USIA MINIMAL KAWIN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2019 ATAS PERUBAHAN UNDANG- UNDANG NOMOR I TAHUN 1974 TENTANG PERKAWINAN DALAM PERSPEKTIF MASLAHAH MURSHALAH - Sunarti, Gustiya (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: This study aims to determine and describe the history of the birth of the marriage law in Indonesia, the meaning and purpose of the minimum age standard for marriage based on Law Number 16 of 2019 in the perspective of maslahah mursalah and the Islamic view of Law Number 16 of 2019 in the perspective of maslahah mursalah. This research is a library research using a qualitative approach. The results of this study indicate that the history of the birth of the marriage law in Indonesia is in the period before independence and the period after independence. The meaning and purpose of the minimum age for marriage based on Law Number 16 of 2019 in the perspective of maslahah mursalah consists of spiritual readiness, physical readiness, financial readiness, mental readiness, socio-emotional readiness, and intellectual readiness. The Islamic view of Law Number 16 of 2019 in the perspective of maslahah mursalah has maslahah for married couples and maslahah for the State/ Government so that it has the benefit of daruriyah. Keywords: Marriage, Law Number 16 of 2019, Maslahah Mursalah. Abstrak: Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan sejarah lahirnya Undang-undang perkawinan di Indonesia, makna dan tujuan standar usia minimal kawin berdasarkan undang-undang Nomor 16 Tahun 2019 dalam perspektif maslahah mursalah dan pandangan Islam terhadap undang-undang Nomor 16 Tahun 2019 dalam perspektif maslahah mursalah. Penelitian ini merupakan Penelitian kepustakaan (library research) dengan menggunakan pendekatan kualitatif. Hasil penelitian ini menunujukkan bahwa Sejarah lahirnya undang-undang perkawinan di Indonesia terdapat pada periode sebelum kemerdekaan dan periode setelah kemerdekaan. Makna dan tujuan standar usia minimal kawin berdasarkan Undang-undang Nomor 16 Tahun 2019 dalam perspektif maslahah mursalah terdiri dari kesiapan spiritual, kesiapan fisik, kesiapan finansial, kesiapan mental, kesiapan sosio-emosional, dan kesiapan intelektual. Pandangan Islam terhadap Undang-undang Nomor 16 Tahun 2019 dalam perspektif maslahah mursalah memiliki maslahah untuk pasangan suami istri dan maslahah untuk Negara/ Pemerintah sehingga memiliki kemaslahatan daruriyah. Kata kunci: Perkawinan, UU Nomor 16 Tahun 2019, Maslahah Mursalah